Sinergi dan Oposisi Biner dalam Praktik Halal Industri Kosmetik dan Farmasi: Kajian Kepustakaan Terstruktur - Ikram, Abdi Dzul Jalal; Sapa, Nasrullah Bin (Fakultas Ekonomi dan Bisnis, Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
This study examines how the concept of halal in the cosmetic and pharmaceutical industries is shaped through the synergy and tension of binary oppositions such as pure–impure, natural–synthetic, scientific–spiritual, and commercial–ethical. Using a structured literature review, the research analyzes academic publications, industrial reports, and halal regulatory frameworks to identify discursive patterns that influence the production and legitimization of halal products. The analysis reveals that halal has undergone a process of meaning commodification, in which religious values are intertwined with narratives of safety, quality, and scientific validation. The findings also show the emergence of hybrid rationalities within certification practices, where fiqh considerations, medical necessity, and industrial logic are negotiated simultaneously. Overall, the study demonstrates that binary oppositions do not operate as fixed boundaries but as flexible mechanisms that shape the identity, justification, and strategic positioning of halal products in the global market.